2009
DOI: 10.1002/jmri.21956
|View full text |Cite
|
Sign up to set email alerts
|

Liver parenchymal enhancement of hepatocyte‐phase images in Gd‐EOB‐DTPA‐enhanced MR imaging: Which biological markers of the liver function affect the enhancement?

Abstract: Purpose: To clarify the factors that predict enhancement of the liver parenchyma in hepatocyte-phase of gadolinium ethoxybenzyl diethylenetriaminepentaacetic acid (Gd-EOB-DTPA)-enhanced MR imaging. Materials and Methods:Gd-EOB-DTPA-enhanced hepatocyte-phase MR images of 198 patients with chronic liver diseases (Child-Pugh class A in 112 patients, class B in 74 patients, and class C in 12 patients) were retrospectively analyzed. The hepatocyte-phase images were obtained using fat-suppressed T1-weighted gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
191
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 224 publications
(196 citation statements)
references
References 18 publications
3
191
1
1
Order By: Relevance
“…the hypercellular area should have less amount of contrast agent in equilibrium-phase, whereas the latter indicates decreased hepatocyte function (11,31,32). In our experience, nodules showing low intensity on hepatocyte-phase gadoxetic acid-enhanced MR images do not always show low density on equilibrium-phase dynamic CT, and vice versa.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…the hypercellular area should have less amount of contrast agent in equilibrium-phase, whereas the latter indicates decreased hepatocyte function (11,31,32). In our experience, nodules showing low intensity on hepatocyte-phase gadoxetic acid-enhanced MR images do not always show low density on equilibrium-phase dynamic CT, and vice versa.…”
Section: Discussionmentioning
confidence: 55%
“…A bolus injection of gadoxetic acid enables the assessment of tumor vascularity on arterial-phase images as well as a functional hepatic (i.e., hepatocyte-phase) images (8,9). The hepatocyte-phase assessments can be performed approximately 20 min after administration of the contrast agent, when approximately 50% of the agent has been taken up by the hepatocytes (10)(11)(12). Studies have shown that the majority of HCCs appear as relatively hypointense lesions on hepatocyte-phase images because of the lack of gadoxetic acid uptake.…”
mentioning
confidence: 99%
“…2 Very high signal intensity on a T 2 -weighted image might help distinguish between hemangioma and liver malignancies, such as metastasis, 3 but gadoxetic acid should not be used when the purpose of the MR examination is to conˆrm a hemangioma diagnosis rather than detect small focal liver lesions. The second disadvantage of gadoxetic acid is that its uptake is not always su‹cient to provide the contrast necessary to distinguish between liver parenchyma and lesions [4][5][6] (Fig. 1a, b).…”
Section: Rules Guiding Use Of Gadoxetic Acidmentioning
confidence: 99%
“…Several clinical parameters, including ChildPugh score, serum bilirubin levels, and indocyanine green test results, are associated with uptake of gadoxetic acid (or signal intensity of the liver on hepatocyte phase images). [4][5][6][7] No known imaging parameter predicts liver enhancement on hepatocyte phase images before gadoxetic acid administration, 7 though liverˆbrosis or stiŠness as measured by MR elastography might indicate insufcient liver enhancement. 8 We suggest using an alternative contrast agent, such as an extracellular GBCA, when previous MR examinations indicate insu‹cient liver enhancement after gadoxetic acid administration.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…In human studies, liver parenchymal enhancement after administration of Gd-EOB-DTPA has been shown to correlate with ICG clearance and with liver cirrhosis as assessed by the CPS [26,27], and subsequent biliary excretion has been shown to be delayed in patients with impaired liver function [28]. In a study of patients with primary biliary cirrhosis, quantitative parameters indicative of liver function derived from DA were shown to correlate with disease severity [29].…”
mentioning
confidence: 99%